The Impact of Digital Marketing on Consumer Purchase Decisions in Kathmandu Valley - Khadka, Deepa (Nepalese Journal of Business, 2025)
This study examines the impact of smartphones on youth of Kathmandu valley. Youth behavior is selected as the dependent variable. Similarly, price brand image product features product quality service quality and customer satisfaction are selected as independent variables. This study is based on primary data with 153 observations. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of different factors influencing impact on youth behavior of Kathmandu valley. The study showed that price has a positive impact on youth behavior. It means that reasonable price lead to an increase in youth behavior. Similarly, brand image has a positive impact on youth behavior. It indicates that a good brand image leads to an increase in youth behavior Moreover, product features have a positive impact on youth behavior. It means that an increase in product features leads to an increase in youth behavior. Likewise, product quality has a positive impact on youth behavior. It shows that the increase in product quality leads to an increase in youth behavior. Further, service quality has a positive impact on youth behavior. It shows that an increase in service quality leads to an increment in youth behavior. However, customer satisfaction has a positive impact on youth behavior. It shows that an increase in customer satisfaction leads to an increment in youth behavior.